Tendinopathy and tendon material response to load: What we can learn from small animal studies. (15th October 2021) - Williamson, Patrick M.; Freedman, Benjamin R.; Kwok, Nicholas; Beeram, Indeevar; Pennings, Jan; Johnson, Jeremy; Hamparian, Daron; Cohen, Emily; Galloway, Jenna L.; Ramappa, Arun J.; DeAngelis, Joseph P.; Nazarian, Ara
Abstract: Tendinopathy is a debilitating disease that causes as much as 30% of all musculoskeletal consultations. Existing treatments for tendinopathy have variable efficacy, possibly due to incomplete characterization of the underlying pathophysiology. Mechanical load can have both beneficial and detrimental effects on tendon, as the overall tendon response depends on the degree, frequency, timing, and magnitude of the load. The clinical continuum model of tendinopathy offers insight into the late stages of tendinopathy, but it does not capture the subclinical tendinopathic changes that begin before pain or loss of function. Small animal models that use high tendon loading to mimic human tendinopathy may be able to fill this knowledge gap. The goal of this review is to summarize the insights from in-vivo animal studies of mechanically-induced tendinopathy and higher loading regimens into the mechanical, microstructural, and biological features that help characterize the continuum between normal tendon and tendinopathy. Statement of significance: This review summarizes the insights gained from in-vivo animal studies of mechanically-induced tendinopathy by evaluating the effect high loading regimens have on the mechanical, structural, and biological features of tendinopathy. A better understanding of the interplay between these realms could lead to improved patient management, especially in the presence of painful tendon. Graphical abstract: Image, graphical abstract